Comparative Growth Analysis of Entire and Meromorphic Functions Using Their Relative Types and Relative Weak Types - Datta, Sanjib Kumar; Biswas, Tanmay (Eurasian Mathematical Journal, 2017)
In this paper we study some comparative growth properties of entire and meromorphic functions on the basis of their relative type and relative weak type.